Wykonaj zadanie 7 z załącznika



Wykonaj Zadanie 7 Z Załącznika class=

Odpowiedź :

Magda

Odpowiedź:

[tex]x=\dfrac{\sqrt{1\frac{7}{9}}-\frac{3}{50}:(0,2)^2+1\frac{2}{3}}{(-2)^3\cdot0,25+2\frac{1}{2}}+\dfrac{1}{3}=\dfrac{\sqrt{\frac{16}{9}}-\frac{3}{50}:(\frac{1}{5})^2+1\frac{2}{3}}{-8\cdot0,25+2\frac{1}{2}}+\dfrac{1}{3}=[/tex]

[tex]=\dfrac{\frac{4}{3}-\frac{3}{50}:\frac{1}{25}+1\frac{2}{3}}{-2+2\frac{1}{2}}+\dfrac{1}{3}=\dfrac{\frac{4}{3}-\frac{3}{\not50_{2}}\cdot\not25^1+1\frac{2}{3}}{\frac{1}{2}}+\dfrac{1}{3}=\dfrac{\frac{4}{3}-\frac{3}{2}+\frac{5}{3}}{\frac{1}{2}}+\dfrac{1}{3}=\\\\\\=\dfrac{\frac{9}{3}-\frac{3}{2}}{\frac{1}{2}}+\dfrac{1}{3}=\dfrac{3-\frac{3}{2}}{\frac{1}{2}}+\dfrac{1}{3}=\dfrac{\frac{6}{2}-\frac{3}{2}}{\frac{1}{2}}+\dfrac{1}{3}=\dfrac{\frac{3}{2}}{\frac{1}{2}}+\dfrac{1}{3}=[/tex]

[tex]=\frac{3}{2}:\frac{1}{2}+\frac{1}{3}=\frac{3}{\not2}\cdot\not2+\frac{1}{3}=3+\frac{1}{3}=3\frac{1}{3}[/tex]